Prática de leitura e escrita na web 2.0: a produção do gênero conto hipermidiático com a ferramenta POWTOON nas aulas de língua portuguesa - ARAÚJO, Jessica de Souza de (UNIFAP – Universidade Federal do Amapá, 2022)
The technological advance enhanced the use of the Internet in the several scopes at school, thus, either the school or the Portuguese Language teacher have the responsibility of promoting new reading and writing practices that involve the use of the 2.0 Web, for, at present, the reader/student has interests related to the new digital technologies and to the virtual environment. Therefore, this research aims to analyze the practice of reading and writing of the literary Genre Hypermedia Tale, produced with the help of the Powtoon tool. As theoretical foundations, the main scholars were utilized: Vygotsky (1998), Brasil (2017), Koch e Elias (2009, 2011), Soares (2002, 2009), Kleiman (1995), Dudeney e Hockly et al (2016), Mattar (2012, 2013), Gotlib (2006) and Santaella (2014). Methodologically, a qualitative research was used, and had, as a starting point, a bibliographic survey about the theme. Afterwards a Research-action was carried out, in which, the subjects involved were 30 students of the 6th grade of a state elementary school, located in the city of Macapá - AP. The analysis corpus is composed of four hypermedia tales based on the literary tale “Pinocchio”, by Carlo Collodi, produced by the participating groups of the research. With the result of the analyses, it was observed that the students appropriated from the constitutive elements of the literary Genre Hypermedia, tale such as Digital Narrative, The Plot with Hypermedia Elements, Climax, Characters, Space, Chronological Time, Hypermedia Language and Collaborative Writing. Besides, the students developed the hypermedia tale from their interaction with the students of their group, and with the help of the researchers, and the Zone of Proximal Development - ZPD (VYGOTSKY, 1998) was important in this process.